1988
DOI: 10.1111/j.1439-0418.1988.tb00594.x
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive strategy of Dinarmus vagabundus Timb. (Hym., Pteromalidae): real sex ratio, sequence of emitting diploid and haploid eggs and effects of inbreeding on progeny

Abstract: One ovipositing adult female D. vagabundus will give rise to three females and one male on the average. In order to test the hypothesis of the preferential death of one sex, we experimentally determined if the sex ratio at ovipositing was the same as that of the emerging adults. Newborn larvae were used after first determining that their number was the same as that of the eggs deposited. When six larvae were transferred to a paralyzed host, there was no selective elimination of larvae by competition between se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 24 publications
2
2
0
Order By: Relevance
“…Sib-sib matings should therefore rapidly yield diploid males since 50 per cent of the diploids in each generation should be homozygous. Results of inbreeding experiments were consistent with these expectations in the few species quoted above but the failure to rapidly obtain diploid males in other Hymenoptera of the chalcidoidean superfamily such as Nasonia vitripennis (Whiting, 1960), Melittobia species (Schmieder & Whiting, 1947) and Dinarmus vàgabundus (Rojas- Rousse et al, 1988) deprives this hypothesis of generality.…”
Section: Introductionsupporting
confidence: 74%
“…Sib-sib matings should therefore rapidly yield diploid males since 50 per cent of the diploids in each generation should be homozygous. Results of inbreeding experiments were consistent with these expectations in the few species quoted above but the failure to rapidly obtain diploid males in other Hymenoptera of the chalcidoidean superfamily such as Nasonia vitripennis (Whiting, 1960), Melittobia species (Schmieder & Whiting, 1947) and Dinarmus vàgabundus (Rojas- Rousse et al, 1988) deprives this hypothesis of generality.…”
Section: Introductionsupporting
confidence: 74%
“…And third, in most instances females tended to produce as many female progeny in the last cell parasitized as in the first (but see below , Table III). Thus, this study joins others (e.g., Sekhar 1957, Gordh and DeBach 1976, Nadel and Luck 1985, Suzuki and Hiehata 1985, Dijkstra 1986, Rojas-Rousse, et al 1988 in supporting the assumption of sex ratio theorists that male parasitoids are fully capable of inseminat-1993] Tepedino 147…”
Section: Discussionsupporting
confidence: 77%
“…Studies of the nutritional balance during the development of the gregarious ectoparasitoid D. vagabundus have shown that the mean weight of both sexes decreases significantly at higher larval densities (Rojas-Rousse et al, 1988). In a population rearing cage with a high level of ovipositing M. dorsiplana females per host, the mean weights of adults emerging from a parasitized host were negatively correlated with egg-clutch size, the larger the egg clutch, the lower the weight.…”
Section: Discussionmentioning
confidence: 98%
“…These persistent pods provide a natural reserve of parasitoids which are a potential resource for the biological control of Bruchidae. Previous investigations have shown that Dinarmus vagabundus and Dinarmus basalis (Pteromalidae), parasitoids of larval and pupal stages of bruchids, can be mass-reared on a substitution bruchid host, Callosobruchus maculatus (Rojas-Rousse et al, 1983;Rojas-Rousse et al, 1988). Some life history traits of M. dorsiplana have been investigated under laboratory conditions using the substitution bruchid host Callosobruchus maculates, and it was observed that with a low density of M. dorsiplana females per host, i.e.…”
Section: Introductionmentioning
confidence: 99%